The Routledge Handbook of Privacy and Social Media - Trepte, Sabine; Masur, Philipp K. (Taylor & Francis, 2023)
This volume provides the basis for contemporary privacy and social media research and informs global as well as local initiatives to address issues related to social media privacy through research, policymaking, and education. Renowned scholars in the fields of communication, psychology, philosophy, informatics, and law look back on the last decade of privacy research and project how the topic will develop in the next decade. The text begins with an overview of key scholarship in online privacy, expands to focus on influential factors shaping privacy perceptions and behaviors - such as culture, gender, and trust - and continues with specific examinations of concerns around vulnerable populations such as children and older adults. It then looks at how privacy is managed and the implications of interacting with artificial intelligence, concluding by discussing feasible solutions to some of the more pressing questions surrounding online privacy. This handbook will be a valuable resource for advanced students, scholars, and policymakers in the fields of communication studies, digital media studies, psychology, and computer science.